Analisis Persepsi, Motivasi, dan Preferensi Berekreasi di Hutan Kota Ciganjur, Jakarta Selatan - Oktovianus, Oktovianus; Anggraini, Tri Hanna Tania; Gantina, Devita; Dira Oktavia, Reno Catelya; Rachmatullah, Adam (Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze visitor perceptions, motivations, and preferences at Ciganjur Urban Forest, South Jakarta, as one of the strategic green open spaces. A descriptive quantitative approach was employed involving 100 respondents through structured questionnaires. Data analysis was conducted descriptively to map respondent behavioral patterns. The findings indicate that primary push motivations include the need for relaxation, creativity restoration, and social bond strengthening, while pull motivations are dominated by peaceful atmosphere and clean air quality. Visitor perceptions of urban forest functions are generally positive, particularly regarding cleanliness, comfort, and ecological benefits. In terms of preferences, prioritized facilities include jogging tracks, park benches, prayer rooms, and fish nursery areas, while gazebos, interpretive signage, and disability-friendly facilities are considered less important. This research confirms that urban forest management should be directed toward user-oriented management approaches while maintaining the balance of ecological, recreational, educational, and inclusive functions. These findings align with Push and Pull Motivation theory and Utility Maximization, reinforcing global studies on the role of urban forests as psychosocial restoration spaces and means of enhancing urban community quality of life. Keywords: urban fores, motivation, perception, preference, urban recreation